O atleta de alto nível e o Escudo de Aquiles: analisando a ressonância da subjetividade contemporânea no herói dos campos e das quadras - Campos, Adriana Fayad (2007)
This research aims at discussing some considerations about contemporary´s subjectivity and it´s link with the identity building in the high performance athlete. Seven interviews were realized, six of them with athletes still on the peak of their careers: 3 soccer players, 3 baskett players; and 1 former soccer player, who played in the Brazilian Soccer Team at the 70´s. The analysis of these interviews helped to make an appreciation on the building of the athlete´s identity in our days, as well as their relationship with their family, the cheerers, sports midia and co-workers. The method applied was a critical review of the psychoanalytical method, called The Multiple Field Theory . This method was applied in both the interviews and their analysis. We can conclude that the fragmentation of the images which figures in the sporting universe, becomes the very essence of the sportsman´s identity, which, due to their lack of time to establish grounded relationships wether are familiar or social ones, find in the imagetic structure its major recognizable seal. That way, it´s formed an almost perfectly conjunction of the two sides of their representational shield. Another point of discussion is the professional sports leading the athlete to a machine-body vision, sometimes making him oscillate between the archetypical role of heroe, and the one of a man with a single and limited vision.